The Arteriovenous Malformation Rupture on Posterior Cranial Fossa:Management and Treatment of 9 Children Patients at Morozovskaya Children's Hospital: Arteriovenous Malformation Rupture on Posterior Cranial Fossa:Management - Zokirjon Utkurovich, Zokhidov; Encarnacion-Santos, Daniel; Chmutin, Gennady; Gordon-Gullanyi, Ayisi; Chmutin, Egor; Livshits , Matvey Igorevich; Levov , Alexander Vyacheslavovich; Berdieva , Madina Golibovna; Shlepotina, Elizaveta Andreevna; Dovran, B. Nurmyradov; Mamatkulov , Sherbek Musakulovich (Talenta Universitas Sumatera Utara, 2025)
Abstract Background Posterior cranial fossa (PCF) arteriovenous malformations (AVM) in children are the least studied among vascular malformations. Mortality rates after hemorrhages from ruptured PCF AVM reach the range of up to 21-67%. The aim of this Evaluation of the treatment tactics of the arteriovenous malformation rupture in an area of the posterior cranial fossa in children. Materials and Methods The study includes 9 children admitted to the Morozovskaya Children’s City Clinical Hospital Moscow Healthcare department, Moscow, Russia, with PCF, AVM intracranial hemorrhage (ICH) during the period of 2015-2022. The age varies from 7 to 17 years old. All patients underwent clinical and neurological examination, CT, and MRI of the brain, as well as cerebral angiography. The volume of intracranial hematoma ranges from 5 to 41.1 mL. To decide on the further extent of surgical intervention, GCS, Greab, PedNIHSS, and H-H scales were used. Results The extent of surgical intervention was based on the time of the admission to the hospital, the severity of the patients’ condition, the size and location of the ICH, and its relationship to the med-stem structures. Type of operation: microsurgical intervention in 3 cases (33.3 %), endovascular embolization in 2 cases (22.2 %), combined treatment in 4 cases (44.5 %). Surgery was performed in the acute period in all patients. Conclusion Modern microsurgical and endovascular PCF AVM treatment methods allow for positive results in complete neurological symptom regression form. This considerably decreases disability rates and increases patients’ quality of life.